Knowledge regarding care of preterm babies among nurses working in a tertiary-level hospital - Shrestha, Susmita; Thapa, Bima; Nepali, Shilpa; Mahat, Pradeep; Subedi, Rashmi (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: A preterm baby is defined as a baby born alive before 37 weeks of pregnancy is completed. Preterm birth is challenging for both the infant and the family. The long-term morbidity of these infants is a serious public health concern. Nurses’ critical thinking, knowledge, qualifications, attitude, and advanced skills are essential to provide good quality services and decrease the mortality and morbidity related to preterm babies. This study aimed to assess nurses’ knowledge of preterm care. Method: Using a descriptive cross-sectional study design with a selfadministered, semi-structured questionnaire, 122 nurses from pediatric and obstetric units from Tribhuwan University Teaching Hospital were enrolled through total enumerative sampling in the study. Result: The study revealed that the majority of respondents (82.8%) had a good level of knowledge about preterm care. The study found a statistically significant association between knowledge and socio-demographic characteristics, specifically current residence area (p = 0.045). Regarding knowledge and profession-related characteristics, the study revealed a significant association between knowledge and total working experience (p = 0.042). Conclusion: In-service education and training on preterm care should be provided to educate nurses and enhance their knowledge of caring for preterm babies. A nurse is a crucial primary care provider, and therefore, her education and access to information on caring for preterm babies will help her provide adequate care and prevent complications.